2013
DOI: 10.1016/j.ijcard.2013.01.255
|View full text |Cite
|
Sign up to set email alerts
|

A prospective validation of the HEART score for chest pain patients at the emergency department

Abstract: The HEART score provides the clinician with a quick and reliable predictor of outcome, without computer-required calculating. Low HEART scores (0-3), exclude short-term MACE with >98% certainty. In these patients one might consider reserved policies. In patients with high HEART scores (7-10) the high risk of MACE may indicate more aggressive policies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
414
10
13

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 445 publications
(484 citation statements)
references
References 33 publications
19
414
10
13
Order By: Relevance
“…The obtained results of our study confirmed that 11% of total patients was in lowrisk group (HEART score 0-3) and had 0% chance for reaching an endpoint (MACE), lower in our study compared with previous studies 2.5% 2 , 0.99% 12 and 1.7% 13 . Based on our results, 48% of total patients was also in intermediate-risk group (HEART score 4-6) and had 14.58% chance for reaching an endpoint (MACE), compared with previous studies, the frequency of patients had chance to reach endpoint in this group were 20.3% 2 , 11.6% 12 and 16.6% 13 .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The obtained results of our study confirmed that 11% of total patients was in lowrisk group (HEART score 0-3) and had 0% chance for reaching an endpoint (MACE), lower in our study compared with previous studies 2.5% 2 , 0.99% 12 and 1.7% 13 . Based on our results, 48% of total patients was also in intermediate-risk group (HEART score 4-6) and had 14.58% chance for reaching an endpoint (MACE), compared with previous studies, the frequency of patients had chance to reach endpoint in this group were 20.3% 2 , 11.6% 12 and 16.6% 13 .…”
Section: Discussionsupporting
confidence: 88%
“…Based on our results, 48% of total patients was also in intermediate-risk group (HEART score 4-6) and had 14.58% chance for reaching an endpoint (MACE), compared with previous studies, the frequency of patients had chance to reach endpoint in this group were 20.3% 2 , 11.6% 12 and 16.6% 13 . The results of this study showed 17% of total patients was in highrisk group (HEART score 7-10) and had 41.46% chance for reaching an endpoint (MACE), lower in our study compared with previous studies 72% 2 , 65.2% 12 and 50.1% 13 .…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Several risk scores have been developed, including Thrombolysis in Myocardial Infarction (TIMI); [4][5][6] Global Registry of Acute Coronary Events (GRACE); [7][8][9][10] Fast Revascularisation in Instability in Coronary disease (FRISC); 11 and History, ECG, Age, Risk factors, and Troponin (HEART), 12,13 to identify which patients with chest pain of cardiac etiology are at higher risk for worse cardiovascular outcomes and mortality. These scores are derived from overlapping clinical variables recorded at time of evaluation, including age, vital signs, comorbidities, and biomarkers.…”
Section: Resultsmentioning
confidence: 99%
“…We intend to follow up with a prospective observational study, likely modifying the new VCP Rule and comparing with other possible clinical rules. 33,34 This could be in combination with pointof-care testing. However, these rules may have more utility when combined with clinical pretest probabilities as indicated by our study.…”
Section: Discussionmentioning
confidence: 99%